Dating the Middle Paleolithic deposits of La Quina Amont (Charente, France) using luminescence methods. Issue 109 (August 2017) - Frouin, Marine; Lahaye, Christelle; Valladas, Hélène; Higham, Thomas; Debénath, André; Delagnes, Anne; Mercier, Norbert
Abstract: The site of La Quina Amont, located in the Charente region, is one of the most important sites in southwestern France for studying major changes in human behaviors from the Middle Paleolithic (MP) to the Early Upper Paleolithic (EUP). Extensively excavated over the past 50 years, numerous dating studies have been focused on the Upper Paleolithic deposits using radiocarbon on bone collagen and thermoluminescence (TL) on heated flints; however, the Mousterian levels remain undated due to the scarcity of suitable materials. Our investigations aimed to provide for the first time a chronological framework for the site using luminescence dating methods on different minerals contained in the sediments. Coarse grains of quartz were dated using the optically stimulated luminescence (OSL) technique, and polymineral fine grains were dated using both infrared (IRSL) and post-infrared (pIR-IRSL) stimulated luminescence signals. OSL, IRSL and pIR-IRSL results were combined with available TL and radiocarbon data sets to propose a chronology for the site. The agreement between these methods provides key insights into the sedimentological processes involved in the site formation and into the chronology of the human occupations. In particular, it shows that the sequence spans almost ∼20, 000 years (20 ka). Moreover, the new chronological framework suggests that the makers of the Quina lithic technocomplex (LTC), who were reindeer hunters, inhabited the site from the end of marine isotope stage (MIS) 4 to the beginning of MIS 3. We also show that Levallois and Discoidal industries occurred successively under temperate paleoclimatic conditions, during MIS 3 but not after ∼40 ka. Finally, we compare the Quina LTC dataset with other sites in southern France in order to shed light upon the variability in Mousterian industries of this region.